Positive Association of Plasma Trimethylamine-N-Oxide and Atherosclerosis in Patient with Acute Coronary Syndrome - Wanwen Kong; Junyi Ma; Ying Lin; Weiyu Chen (Hindawi-Wiley, 2022)
Aim. Atherosclerosis is the major cause of acute coronary syndrome (ACS) which is a significant contributor to both morbidity and mortality in the world. The microbiome-derived metabolite trimethylamine-N-oxide (TMAO) has aroused great interest and controversy as a risk factor of atherosclerosis. Therefore, in this study, we aimed at investigating whether plasma TMAO can be a risk factor of atherosclerosis in coronary artery of patients with ACS and how this relates to lipids and proinflammatory cytokines in plasma. Methods. We enrolled consecutive patients with ACS who underwent percutaneous coronary intervention (PCI). Gensini scoring was used to evaluate angiographic atherosclerosis in the coronary artery of the patients. 13 patients were divided into low (Gensini score<25), 33 into intermediate (Gensini score 25-50), and 81 into severe atherosclerosis (Gensini score ≥50). Plasma TMAO, vasculitis factors, and cardiovascular biomarkers were measured by clinical biochemistry, intima-media thickness (IMT) of carotid artery was determined by the Color Doppler ultrasound, and the atherosclerotic lesion in coronary artery was assessed in PCI. Results. Plasma TMAO concentrations were positively associated with Gensini score (OR=0.629, p<0.001) and Gensini subgroup (R=0.604, p<0.001). Plasma TMAO concentrations in patients with severe coronary atherosclerosis were higher than those of patients with moderate coronary atherosclerosis, and the plasma TMAO concentrations of patients with moderate coronary atherosclerosis were higher than those of patients with mild coronary atherosclerosis, the difference was statistically significant [4.73 (3.13, 4.62) versus 1.13 (0.63, 3.34) versus 0.79 (0.20, 1.29), p<0.001], respectively. Furthermore, ROC analysis showed that plasma TMAO could identify the severity of atherosclerosis (p<0.001). The AUC of TMAO for severe atherosclerosis was 0.852 (95%CI=0.779−0.925). The sensitivity and specificity of TMAO for identifying severe atherosclerosis are 96.3% and 63.0% when the cut-off value of TMAO was set at 1.2715 pg/ml. Furthermore, logistic regression analysis showed plasma TMAO concentrations were positively associated with severity of atherosclerosis in coronary artery (OR=1.934, 95%CI=1.522−2.459, p<0.001). For all that, negatively association was observed between TMAO and age (OR=−0.224, p<0.05), B-type natriuretic peptide (BNP) (OR=−0.175, p<0.05), and interleukin-8 (IL-8) (OR=−0.324, p<0.001), while positive association was observed between TMAO and nitric oxide (NO) (OR=0.234, p<0.01). However, there is no obvious association was observed between Gensini score and cardiovascular biomarkers, vasculitis factors, and carotid IMT, respectively. Conclusion. Our cross-sectional observation suggested that plasma TMAO concentrations positively associated with coronary atherosclerosis in ACS patients and serve as a risk factor for severe atherosclerosis. Plasma TMAO also correlated with age, BNP, IL-8, and NO. However, no obvious association was found between atherosclerosis with vasculitis factors and cardiovascular biomarkers in this study, and there was no conclusive evidence showing TMAO enhance atherosclerosis via regulation of inflammation or lipid.